Modeling the Response of the Langtang Glacier and the Hintereisferner to a Changing Climate Since the Little Ice Age - Wijngaard, René R.; Steiner, Jakob F.; Kraaijenbrink, Philip D. A.; Klug, Christoph; Adhikari, Surendra; Banerjee, Argha; Pellicciotti, Francesca; van Beek, Ludovicus P. H.; Bierkens, Marc F. P.; Lutz, Arthur F.; Immerzeel, Walter W. (Frontiers in Earth Science, 2019)
This study aims at developing and applying a spatially-distributed coupled glacier mass balance and ice-flow model to attribute the response of glaciers to natural and anthropogenic climate change. The model includes a novel spatially-distributed formulation of the Shallow Ice Approximation that does not require a priori information about the flowline geometry of glaciers. We focus on two contrasting glaciers: a debris-covered glacier (Langtang Glacier in Nepal) and a clean-ice glacier (Hintereisferner in Austria). The model is applied from the end of the Little Ice Age (1850) to the present-day (2016) and is forced with four representative bias-corrected General Circulation Models (GCMs) from the historical experiment of the CMIP5 archive. For the selected GCMs, runs are selected with and without further anthropogenic forcing after 1980 until 2016 to isolate the effects of human-induced climate change on glacier mass balance and flow. The outcomes indicate that both glaciers experience the largest reduction in area and volume under warm climate conditions, whereas area and volume reductions are smaller under cold climate conditions. Simultaneously with changes in glacier area and volume, surface velocities generally decrease over time. Without further anthropogenic forcing the results reveal a 3% (8%) smaller decline in glacier area (volume) for the debris-covered glacier and a 26% (76%) smaller decline in glacier area (volume) for the clean-ice glacier. The difference in the magnitude between the two glaciers can mainly be attributed to differences in the response time of the glaciers, where the clean-ice glacier shows a much faster response to climate change. We conclude that the response of the two glaciers can mainly be attributed to anthropogenic climate change and that the impact is larger on the clean-ice glacier. The outcomes show that the model performs well under different climate conditions and that the developed approach can be used for regional-scale glacio-hydrological modelling.